2013
DOI: 10.1002/2012jb009953
|View full text |Cite
|
Sign up to set email alerts
|

Stress magnitude and orientation in the Potiguar Basin, Brazil: Implications on faulting style and reactivation

Abstract: [1] We analyzed borehole breakout data and drilling-induced tensile fractures derived from resistivity image logs run at 10 oil wells to derive the orientation of the maximum horizontal stress S Hmax from the Potiguar Basin in the continental margin of Brazil. Stress magnitudes are derived from density logs for the vertical stress, mini-frac tests for the minimum horizontal stress S hmin , and rock strength laboratory analysis to estimate the S Hmax magnitudes. We compared these results with the stress regime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 70 publications
(156 reference statements)
0
25
1
6
Order By: Relevance
“…Five data sets were obtained from carbonate pavements located in Brazil, which we refer to as "Brazil I" to "Brazil V" . These pavements are part of a subhorizontal postrift carbonate sequence (the Albian Jandaíra Formation), deposited in the Potiguar basin in northeast Brazil [Reis et al, 2013]. Although these pavements are located in the same structural domain, they display fracture networks with different spatial distributions.…”
Section: Application To Realistic Multiscale Fracture Network 241mentioning
confidence: 99%
“…Five data sets were obtained from carbonate pavements located in Brazil, which we refer to as "Brazil I" to "Brazil V" . These pavements are part of a subhorizontal postrift carbonate sequence (the Albian Jandaíra Formation), deposited in the Potiguar basin in northeast Brazil [Reis et al, 2013]. Although these pavements are located in the same structural domain, they display fracture networks with different spatial distributions.…”
Section: Application To Realistic Multiscale Fracture Network 241mentioning
confidence: 99%
“…We thus cast our eyes briefly towards the southeast margin of Brasil, where both the concepts of hyperextension (Zalán et al, 2011) and a strikingly similar seismological model (Assumpção et al, 2011) have recently been proposed. Lima et al (1997) suggested that offshore sediment loading on the continental shelf can produce the coast-parallel Sh max observed in borehole breakouts from the onshore parts of many marginal basins (see Reis et al, 2013). Lima et al (1997) also proposed that local sources of stress at the eastern continental margin may have been underestimated in the theoretical stress models of the South American plate.…”
Section: Stress and Modes Of Tapermentioning
confidence: 99%
“…During this latest evolution, both the eastern and equatorial passive margins of the South American plate were under compression and strike−slip deformation (Ferreira et al, 2008;Reis et al, 2013). This stress regime is still effective at the present time (Bezerra et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%